2023
DOI: 10.3390/cells12040598
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Blast Crisis Using Mutagenized Chronic Myeloid Leukemia-Derived Induced Pluripotent Stem Cells (iPSCs)

Abstract: Purpose: To model CML progression in vitro and generate a blast crisis (BC-CML) model in vitro in order to identify new targets. Methods: Three different CML-derived iPSC lines were mutagenized with the alkylating agent ENU on a daily basis for 60 days. Cells were analyzed at D12 of hematopoietic differentiation for their phenotype, clonogenicity, and transcriptomic profile. Single-cell RNA-Seq analysis has been performed at three different time points during hematopoietic differentiation in ENU-treated and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Developing new therapeutic tools against AP/BP-CML is therefore an unmet medical need in this life-threatening step of CML. We and others have shown previously the involvement of CD25 as a biomarker detected in primary BP-CML ( 14 , 20 ) as well as its expression in in vitro BP-CML models ( 21 ). These findings prompted us to design CAR-NK to target CD25 as an off—the—shelf immunotherapy for CML blast crisis.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Developing new therapeutic tools against AP/BP-CML is therefore an unmet medical need in this life-threatening step of CML. We and others have shown previously the involvement of CD25 as a biomarker detected in primary BP-CML ( 14 , 20 ) as well as its expression in in vitro BP-CML models ( 21 ). These findings prompted us to design CAR-NK to target CD25 as an off—the—shelf immunotherapy for CML blast crisis.…”
Section: Discussionmentioning
confidence: 70%
“…We have previously shown that CD25 is overexpressed in BP-CML model generated from patient-specific induced pluripotent stem cells (iPSC) and confirmed the increase of its expression during CML progression ( 21 ). These findings prompted us to evaluate the possibility of targeting this receptor using chimeric antigen receptor (CAR)-based therapy in the setting of CML.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…[1] Chronic myeloid leukemia (CML) is a myeloproliferative disease that starts in hematopoietic systems and migrates to other organs of the body. [2] Breast cancer is the most prevalent tumor affecting women and has become the most commonly diagnosed cancer accounting for 11.7 % of total new cases in 2020. [3] Within different subtypes of breast cancer, triple negative breast cancer (TNBC) is the most aggressive and deadly subtype due to its aggressive biology and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer remains a great social burden, causes serious threat to human health throughout the world [1] . Chronic myeloid leukemia (CML) is a myeloproliferative disease that starts in hematopoietic systems and migrates to other organs of the body [2] . Breast cancer is the most prevalent tumor affecting women and has become the most commonly diagnosed cancer accounting for 11.7 % of total new cases in 2020 [3] .…”
Section: Introductionmentioning
confidence: 99%